2016
DOI: 10.17219/acem/36459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol on the Liver Oxidative-Antioxidant Balance in a Rat Model of Parkinson’s Disease

Abstract: ing potentiation of lipid peroxidation, reduction in the concentrations of reduced glutathione and antioxidant enzyme activity, increased malondialdehyde concentration, and disruption of iron metabolism. Environmental toxins and genetic disorders associated with apoptosis and protein breakdown may also play a role [2,3]. Oxidative stress leads to the damage of extremely sensitive neurons and is an important factor in both the initiation and progression of PD. This damage is revealed by increases in either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The rat models of Parkinson’s disease were constructed in accordance with the research of Romuk et al [2], and the behavior test was conducted 8 weeks after 6-OHDA injection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rat models of Parkinson’s disease were constructed in accordance with the research of Romuk et al [2], and the behavior test was conducted 8 weeks after 6-OHDA injection.…”
Section: Methodsmentioning
confidence: 99%
“…PD affects approximately 1% of the population aged 55 years and older; a positive correlation was found between the risk of PD and age [2]. PD is characterized by motor symptoms including postural disturbance, akinesia, tremor, rigidity, and hypokinesia as well as non-motor symptoms including sleep disturbance, pain, apathy, depression, and constipation [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inducible nitric oxide synthase (iNOS) is also reported to be linked to neuroinflammatory responses operative in PD and other neurodegenerative disorders . Although multiple risk factors, such as environmental factors, genetic susceptibility, and aging, are involved in the occurrence and progression of PD, the pathogenesis still remains unclear . Thus this calls for newer and more accurate predictors to help provide better diagnosis and prognosis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 As a commonly used intravenous anesthetic, propofol has a strong antioxidant capacity, and may improve the antioxidant capacity of red blood cells and tissues in rats. 22,23 Our study demonstrated that tyrosine phosphorylation levels of Tyr-IRb and Tyr-IRS1 in the P group were higher than those the I/R group, indicating that an improvement in insulin signaling may result in reduced hyperglycemia.…”
Section: Discussionmentioning
confidence: 69%